2007
DOI: 10.1002/rra.985
|View full text |Cite
|
Sign up to set email alerts
|

Using wavelet analysis to detect changes in water temperature regimes at multiple scales: effects of multi‐purpose dams in the Willamette River basin

Abstract: Maintaining the natural complexity of water temperature regimes is a key to maintaining diverse biological communities. Insect communities, food webs, and fish respond to the magnitude and duration of water temperature fluctuations. Disruption of these natural patterns has the potential to alter physiological processes, behavioural adaptations, and community structure and dynamics. We analysed multiple >300-day time series of water temperature from the Willamette River basin, Oregon, to assess the impact of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 22 publications
(21 reference statements)
4
69
0
Order By: Relevance
“…The insufficiency of a simplifying model or rule of thumb is not necessarily worthy of interest; however, this simplifying model has led us to ignore a critical element of riverine thermal regimes, temporal variability, which is simultaneously being altered v www.esajournals.org through multiple anthropogenic activities including dam-building (Steel and Lange 2007) and climate change (Webb andNoblis 1995, Schär et al 2004). We have demonstrated that, in fish, thermal regimes which might appear similar with respect to mean temperature or total degree days may produce important differences in emergence timing and/or physiological status at emergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insufficiency of a simplifying model or rule of thumb is not necessarily worthy of interest; however, this simplifying model has led us to ignore a critical element of riverine thermal regimes, temporal variability, which is simultaneously being altered v www.esajournals.org through multiple anthropogenic activities including dam-building (Steel and Lange 2007) and climate change (Webb andNoblis 1995, Schär et al 2004). We have demonstrated that, in fish, thermal regimes which might appear similar with respect to mean temperature or total degree days may produce important differences in emergence timing and/or physiological status at emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change, dams, irrigation, and landscape conversion are all agents of changing stream and river thermal regimes that can lead to altered variance (Webb and Noblis 1995, Schär et al 2004, Steel and Lange 2007. It is well-understood both that increased water temperatures speed up metabolic rates of aquatic organisms and, therefore, alter the timing of life-history transitions such as egg hatching and fry emergence and that there are lethal thermal thresholds for many species.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, they can change and influence the aquatic environment and ecology of the river valley where they are built. Specifically, water temperature, which is critical to aquatic flora and fauna [1,2], changes considerably after a reservoir is impounded [3][4][5][6][7][8][9][10]. In addition, the temperature in the downstream reach of a reservoir varies due to the impacts from the releases of this reservoir [3,[5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Hydro-peaking may cause similar rapid and frequent changes to the water temperature, known as thermo-peaking (Toffolon et al 2010). Zolezzi et al (2011) have derived methods for identifying thermo-peaking events, while Steel & Lange (2007) have described the scale, variability, and recurrence of thermo-peaking. The ecological responses to rapid changes in water temperature are, however, not thoroughly studied and understood, with exceptions such as Bruno et al (2013) that studied the effect on the benthic community.…”
Section: Introductionmentioning
confidence: 99%